From subways to product labels: The commercial incorporation of hip hop graffiti - Lombard, Kara-Jane (Taylor and Francis, 2013)
Once described as a terrorist act, hip-hop graffiti has been increasingly appropriated by commercial, art, and government institutions. This article explores one aspect of its mainstreaming, the commercial, breaking with previous scholarship which has stressed the exploitative and degenerative effect of commercial culture on graffiti. It refers to creative industries literature and the scholarship of economist Tyler Cowen to demonstrate that although commercial incorporation can change the graffiti aesthetic and exploit it, increasingly the commercialization of graffiti is a collaborative process. It also finds that often graffiti writers will compromise in one area to obtain rewards in another. Despite increased appropriation, it is evident that ambiguity continues to pervade the meanings of graffiti, indicating that this has not rendered it insignificant or meaningless.